Penerapan Pendekatan Matematika Realistik Indonesia (PMRI) terhadap Kemampuan Pemecahan Masalah Siswa - Elya Rosalina; Novianti Mandasari (Jurnal Pendidikan Matematika:Judika Education, 2021)
This study aims to determine the Problem Solving Ability of Elementary School Class Students after the Indonesian Realistic Mathematics Approach (PMRI) was applied. This research is a quantitative research using experimental methods. The sampling technique used was a random sample technique. Where for the sampling method, which is drawn, the names that come out when drawn will be agreed to serve as the experimental class. This research consists of one independent variable, namely the Indonesian Realistic Mathematics Approach (PMRI), and the dependent variable is Problem Solving Ability. The subjects of this study were third grade students of SD 3 Lubuklinggau. Data collection is done by test technique. The data obtained were then analyzed using the t-test. After the data was analyzed using the t-test at a significant level of 5%, it was obtained tcount (7.57) > ttable (1.672), so it can be said that there was an increase in the problem solving ability of third grade students at SD Negeri 3 Lubuklinggau after the Indonesian Realistic Mathematics Approach (PMRI) was applied. . In conclusion, there is an increase in the problem solving ability of elementary school students after the implementation of the Indonesian Realistic Mathematics (PMRI) approach. Keywords: Indonesian Realistic Mathematics Approach (PMRI), Problem Solving Ability